2018
DOI: 10.1080/21691401.2018.1468339
|View full text |Cite
|
Sign up to set email alerts
|

Improved oral bioavailability of magnolol by using a binary mixed micelle system

Abstract: The aim of this study was to prepare two novel magnolol (MO)-loaded binary mixed micelles (MO-M) using biocompatible copolymers of Soluplus (SOL) and Solutol HS15 (HS15), SOL and d-alpha-tocopheryl polyethylene glycol 1000 succinate (TPGS), to improve magnolol's poor solubility and its oral bioavailability. The organic solvent evaporation method was used to obtain two MO-M by optimization; one was prepared by using SOL and HS15 (MO-H), and the other was prepared by using SOL and TPGS (MO-T). The entrapment eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Since mixed Soluplus ® -Solutol ® HS15 micelles (SSM) are a standard and conventional nanoformulations widely used for application in biopharmaceutical studies [ 49 , 60 ] in this work the ability of SSM to improve the inhibitory role of TQ on human SH-SY5Y neuroblastoma cell migration was explored.…”
Section: Resultsmentioning
confidence: 99%
“…Since mixed Soluplus ® -Solutol ® HS15 micelles (SSM) are a standard and conventional nanoformulations widely used for application in biopharmaceutical studies [ 49 , 60 ] in this work the ability of SSM to improve the inhibitory role of TQ on human SH-SY5Y neuroblastoma cell migration was explored.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro release test showed that MG had sustained release behavior after being encapsulated in micelles. The permeability of MG through the Caco-2 cell monolayer was enhanced, and the relative bioavailability of oral MG-M was 2.83 times higher than that of the raw MG (Shen H et al, 2018). It can be seen that the mixed micelle drug delivery system can improve the poor water solubility and bioavailability of MG.…”
Section: Bioavailability and Formulationmentioning
confidence: 93%
“…Mixed Soluplus (SOL) and Solutol HS15 (HS15), SOL, and D-alpha-tocopheryl polyethylene glycol 1,000 succinate (TPGS) were used to prepare MG-loaded mixed micelles (MG-M) MG-H and MG-T, respectively. The relative oral bioavailability of MG-T and MG-H were increased by 2.39-and 2.98-fold, respectively, compared to that of raw MG, indicating that MG-H and MG-T could promote the absorption of MG in the gastrointestinal tract (Ding et al, 2018). Shen et al also prepared MG-M by pluronic F127 and L61, and its drug loading efficiency and entrapment efficiency were 81.57 ± 1.49% and 27.58 ± 0.53%, respectively.…”
Section: Bioavailability and Formulationmentioning
confidence: 97%
See 1 more Smart Citation
“…Phosphotungstic acid solution, sodium phosphate monobasic and In addition to the pharmacological actions described above, several preclinical studies have shown that magnolol and honokiol are also effective against different types of cancer such as lung, prostate, breast, gall bladder, colon, skin, and hepatocellular carcinoma [20,21]. However, their potential use in clinical applications is restricted by their very low oral bioavailability [17,22,23] Magnolol and honokiol are commercially available as pure substances isolated from magnolia extracts. In the solid state, both compounds show a high degree of crystallinity, with melting points around 102 • C (magnolol) and 87 • C (honokiol) [24][25][26].…”
Section: Reagentsmentioning
confidence: 99%